Analisa Performa Perusahaan Properti dengan Menggunakan Multi Rasio - pandu adi cakranegara (Universitas Muhammadiyah Semarang, 2021)
The development of the population and the increasing middle class have made the demand for property increase in Indonesia. This trend is an opportunity for property companies in Indonesia to sell more properties. Property management can meet this demand, among others, by developing new areas or selling in developed areas at a premium. Each choice will have consequences and will create a trade-off. Therefore this study examines the factors that drive the profitability of the company. The hope is that by focusing on the factors that drive profitability, the company will get the optimum return. The research method used in this research is a quantitative method using multiple linear regression. The research data is secondary data taken from the company's financial statements for 2015 to 2019. This study's findings are that internal factors and external factors both influence the profitability of property companies. This study found four internal factors and one internal factor that affect profitability. Internal factors consist of Debt to Equity Ratio, Net Profit Margin, Total Assets Turnover and Operating Cash Flow. Meanwhile, the external factor that influences it is the interest rate. Managers can focus on these factors to achieve the optimum level of profitability.